Doing qualitative research in psychology a practical guide - Forrester, Michael A.; Sullivan, Cath (SAGE Publications, Inc., 2019)
Providing a complete introduction to qualitative methods in psychology, this textbook is ideal reading for anyone doing a research methods course in psychology that includes qualitative approaches or someone planning a practical project using qualitative methods. Not just another research methods book, Doing Qualitative Research in Psychology is more a 'how to do it' manual, linked with a specifically designed set of digitised video recordings, transcripts and online resources to make learning about qualitative methods as easy as possible. The primary resources are a set of online, publically.